2017
DOI: 10.1161/circep.116.004742
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Incidentally Identified Variants in Genes Associated With Catecholaminergic Polymorphic Ventricular Tachycardia in a Large Cohort of Clinical Whole-Exome Genetic Test Referrals

Abstract: Background The rapid expansion of genetic testing has led to increased utilization of clinical whole exome sequencing (WES). Clinicians and genetic researchers are being faced with assessing risk of disease vulnerability from incidentally identified genetic variants which is typified by variants found in genes associated with sudden death-predisposing CPVT. We sought to determine whether incidentally identified variants in genes associated with catecholaminergic polymorphic ventricular tachycardia (CPVT) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…Landstrom et al 29 demonstrated in whole-exome sequencing, incidentally identified catecholaminergic polymorphic VT-associated variants showed a 9% prevalence, but these variants were of undetermined significance, and in the absence of a clinical suspicion of catecholaminergic polymorphic VT, are unlikely to represent markers of true catecholaminergic polymorphic VT pathogenicity.…”
Section: Cathecholaminergic Polymorphic Vtmentioning
confidence: 99%
“…Landstrom et al 29 demonstrated in whole-exome sequencing, incidentally identified catecholaminergic polymorphic VT-associated variants showed a 9% prevalence, but these variants were of undetermined significance, and in the absence of a clinical suspicion of catecholaminergic polymorphic VT, are unlikely to represent markers of true catecholaminergic polymorphic VT pathogenicity.…”
Section: Cathecholaminergic Polymorphic Vtmentioning
confidence: 99%
“…These results demonstrate that variant frequency in the WES cohort, similar to the control cohort, was driven by contributions from variants in genes that are rarely associated with ARVC cases. Given evidence that disease-specific S:N calculations can distinguish background genetic noise from true pathologic variant burden, this analysis was applied to each gene locus (Landstrom et al, 2017(Landstrom et al, , 2018 Figure 3).…”
Section: Gene-specific Yield With the Wes Cohort In Comparison To Cmentioning
confidence: 99%
“…We have previously shown that amino acid-level S:N can distinguish incidentally identified from pathologic variants based on primary sequence location in genes associated with cardiac channelopathic disease (Landstrom et al, 2017(Landstrom et al, , 2018. We applied this methodology to ARVC-associated gene products.…”
Section: Amino Acid-level Signal-tonoise Analysismentioning
confidence: 99%
“…The same gene can also cause multiple cardiomyopathy subtypes, as seen in TTN (ARVC, DCM, LVNC), LMNA (DCM, HCM, restrictive cardiomyopathy), and DSP (ARVC, DCM) . Further, while increasingly expansive clinical gene testing has allowed more sensitive detection of variants, there has been a rapid increase in the number of “variants of unknown significance” (VUSs) and increased uncertainty in test interpretation . Two phenomenon known to result in non‐Mendelian inheritance of genetic disease further complicate the analysis: (a) Compound heterozygosity whereby two different mutant alleles in the same gene can cause disease in a heterozygous state and (b) multigenic disease whereby multiple mutant alleles in different genes cause disease when each in isolation is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 Further, while increasingly expansive clinical gene testing has allowed more sensitive detection of variants, there has been a rapid increase in the number of "variants of unknown significance" (VUSs) and increased uncertainty in test interpretation. 10 Two phenomenon known to result in non-Mendelian inheritance of genetic disease further complicate the analysis: (a) Compound heterozygosity whereby two different mutant alleles in the same gene can cause disease in a heterozygous state and (b) multigenic disease whereby multiple mutant alleles in different genes cause disease when each in isolation is insufficient. Here, we present a case of mixed cardiomyopathy, with pathologically confirmed characteristics of DCM, ARVC, and LVNC, in the context of multiple VUSs in PKP2, PKP4, SYNE2, and TTN.…”
Section: Introductionmentioning
confidence: 99%